Loss of neuronal network resilience precedes seizures and determines the ictogenic nature of interictal synaptic perturbations. (December 2018) - Chang, Wei-Chih; Kudlacek, Jan; Hlinka, Jaroslav; Chvojka, Jan; Hadrava, Michal; Kumpost, Vojtech; Powell, Andrew; Janca, Radek; Maturana, Matias; Karoly, Philippa; Freestone, Dean; Cook, Mark; et al.
Abstract The mechanism of seizure emergence and the role of brief interictal epileptiform discharges (IEDs) in seizure generation are two of the most important unresolved issues in modern epilepsy research. We found that the transition to seizure is not a sudden phenomenon, but is instead a slow process that is characterized by the progressive loss of neuronal network resilience. From a dynamical perspective, the slow transition is governed by the principles of critical slowing, a robust natural phenomenon that is observable in systems characterized by transitions between dynamical regimes. In epilepsy, this process is modulated by synchronous synaptic input from IEDs. IEDs are external perturbations that produce phasic changes in the slow transition process and exert opposing effects on the dynamics of a seizure-generating network, causing either anti-seizure or pro-seizure effects. We found that the multifaceted nature of IEDs is defined by the dynamical state of the network at the moment of the discharge occurrence. How seizures emerge in epileptic brain remains an enigma. The authors show that the transition to seizure follows a ubiquitous dynamical principle inherent to many processes in nature characterized by repeated transitions between contrasting regimes.